The body in the mind: The bodily basis of meaning, imagination, and reason - Johnson, Mark (Chicago The University of Chicago Press, 1987)
There are booksfew and far betweenwhich carefully, delightfully, and genuinely turn your head inside out. This is one of them. It ranges over some central issues in Western philosophy and begins the long overdue job of giving us a radically new account of meaning, rationality, and objectivity."Yaakov Garb,San Francisco Chronicle